KONSEP KEADILAN DALAM POLIGAMI MENURUT AGAMA ISLAM - Sayyidah Sayyidah; Imas Kania Rahman; Amir Tengku Ramly (Universitas Ibn Khaldun Bogor, 2021)
This article focuses on the discussion of the Kagian Islam on justice in polygamy, namely; what are the requirements for polygamy according to the priests of the mazhab, how the arguments and laws of the priests of the mazhab allow polygamy, and how is it relevant to polygamy according to the contemporary context in Indonesia. This research is a library research (Library Reserach), which is a method of collecting data such as the books of the priests of the mazhab and books that are relevant to the issues discussed. This research is a descriptive analysis, which describes, studies and analyzes the opinions of the Imam of the Schools in terms of being fair in polygamy. The results showed that in Islam it is permissible for a husband to practice polygamy on the condition that he believes or has a strong suspicion that he is able to do justice to his wives. as indicated by the al-Qur'an in the letter al-Nisa